The Effect Of Work Environment And Leadership Style On Job Satisfaction Of Employees At Pagelaran Public Health Center Of Pringsewu Regency - Milan Juliyana; Yenny Marthalena (STIE AMKOP, 2025)
This study aims to analyse the effect of work environment and leadership style on job satisfaction among employees at Pagelaran Public Health Center of Pringsewu Regency of Lampung Province. The background of this research is based on the importance of creating a conducive work environment and implementing an effective leadership style to enhance employee job satisfaction as one of the supporting factors for organizational performance. This research employed a descriptive quantitative approach. The population consisted of all 80 employees at Pagelaran Public Health Center, with a sample of 79 respondents selected using the saturated sampling technique. Data were collected through questionnaires and analysed using multiple linear regression with the assistance of SPSS version 23.The results showed that, partially, the work environment variable had a significant effect on job satisfaction, and leadership style also had a significant effect on employee job satisfaction. Simultaneously, both work environment and leadership style had a positive and significant effect on job satisfaction. The coefficient of determination (R²) indicated that 30.3% of the variation in job satisfaction could be explained by the work environment and leadership style, while the remaining 69.7% was influenced by other factors not examined in this study.